Organizacja i funkcjonowanie Trybunału Konstytucyjnego - Siemieński, Feliks (Wydział Prawa i Administracji UAM, 1986)
The subject matter of the article is the regulation of the Constitution of Polish People's Republic, the Constitutional Tribunal Act (CT) of 29 Apr. 1985 and the resolution of the Polish Seym of 31 Jul. 1985 on the specific proceedings before the CT, concerning several problems marked in the title. The author advocates his opinion in the following questions: 1. Relation of the quoted resolution to the CT Act. The author maintains that the regulation of the resolution should be contained in the Act. 2. Membership and the mode of constituting the CT, conditions to be fulfilled by the candidates to become appointed members, possibilities of revokinf the CT judges. 3. Questions of independence of the judges, their subordination and the judicial immunity, the author advocates here that contrary to the explicit Constitutional regulation, the CT judges are subordinated not only to the Constitution but also to parliamentary statutes and resolutions. 4. The range of subjects entitled to apply to the CT to decide on the legality of regulation, and the formal requirements concerning the said applications; the author advocates that citizens are not ellegible to apply directly to the CT but they can influence the activity of the state organs and social organizations. 5. The range of subjects entitled to address legal queries to the CT, the mode of proceedings, deciding and effects of the CT decisions in that scope. 6. Next, trails before the CT, benches, final character of the CT decisions, possibility of trials de novo in cases decided by the CT in the full composition of its bench, character of the general meeting of the CT judges. 7. The final part dwells on the CT decisions, their formal requirements, legal effects of the decisions and the mode of their execution.
Organization and functioning of the Constitutional Tribunal